Reformation readings of Paul: explorations in history and exegesis - Allen, R. Michael; Linebaugh, Jonathan A. (IVP Academic, 2015)
Did the Protestant Reformers understand Paul correctly? Has the church today been unduly influenced by Reformation-era misreadings of the Pauline epistles? These questions - especially as they pertain to Martin Luther's interpretation of the Pauline doctrine of justification - have been at the forefront of much discussion within biblical studies and theology in light of the New Perspective on Paul. But that leads to another question: Have we understood the Reformers correctly? With that in mind, these essays seek to enable a more careful reading of the Reformers' exegesis of Pauline texts. Each chapter pairs a Reformer with a Pauline letter and then brings together a historical theologian and a biblical scholar to examine these Reformation-era readings of Paul. In doing so, this volume seeks a better understanding of the Reformers and the true meaning of the biblical text. --Publishers